The Third Reich's intelligence services the career of Walter Schellenberg - Paehler, Katrin (Cambridge University Press, 2017)
"This is the first-ever analytical study of Nazi Germany's political foreign intelligence service, Office VI of the Reichssicherheitshauptamt and its head, Walter Schellenberg. Katrin Paehler tells the story of Schellenberg's career in policing and intelligence, charts the development and activities of the service he eventually headed, and discusses his attempts to place it at the center of Nazi foreign intelligence and foreign policy. The book locates the service in its proper pedigree of the SS as well as in relation to its two main rivals - the Abwehr and the Auswärtige Amt. It also considers the role Nazi ideology played in the conceptualization and execution of foreign intelligence, revealing how this ideological prism fractured and distorted Office VI's view of the world. The book is based in contemporary and postwar documents - many recently declassified - from archives in the United States, Germany, and Russia."...Provided by publisher
Includes bibliographical references and index. Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Schellenberg, Walter -- 1910-1952; Nationalsozialistische Deutsche Arbeiter-Partei -- Schutzstaffel -- Reichssicherheitshauptamt; Nationalsozialistische Deutsche Arbeiter-Partei -- Schutzstaffel -- Sicherheitsdienst; Nationalsozialistische Deutsche Arbeiter-Partei -- Schutzstaffel -- Biography; Deutsches Reich -- Reichssicherheitshauptamt -- Amt VI, Auslandsnachrichtendienst; Geschichte 1934-1945; Weltkrieg (1939-1945); World War, 1939-1945 -- Secret service -- Germany; Nazis -- Biography; Intelligence officers -- Germany -- Biography; Deutschland; Biografie